Feasibility of bulk shipping investment - investment into the supramax segment with time horizon 2023 - 2027 - Lee, Yu Cheng (Nanyang Technological University, 2022)
This paper strives to give a comprehensive study into the feasibility of investment in the Supramax segment from 2023-2027 and provide a recommendation on whether to enter the segment. This paper is the first of three volumes and is to be read in sequence.